Calibration of 0D/1D models based on OBD data for quick remapping of SI engine ECUs - Adrian Irimescu; Simona Silvia Merola (MethodsX, 2025)
Use of alternative energy sources in internal combustion engines requires modifying the electronic control unit (ECU) software compared to standard fuels such as gasoline or diesel. This is often called “remapping” and is usually approached through a combination of numerical and experimental techniques. In the case of spark ignition (SI) power units the new set of control settings is focused on “maps” that contain parameters such as injection duration and ignition timing; within this context, the proposed method concentrates on the use of 0D/1D modeling. A new model calibration procedure was developed for achieving acceptable accuracy by using original equipment manufacturer (OEM) ECU data acquired through the on-board diagnostic (OBD) port. The core assumption is that existing control parameters can be used for calibrating a 0D/1D model of the power unit; validation was achieved by using data recorded on two SI power units. The main advantage compared to the existing calibration procedures is that time- and cost-effective ECU remapping can be achieved with acceptable accuracy, even for fuels with properties that are quite different compared to gasoline, such as H2. • 0D/1D model calibration based on OBD data recorded on an OEM ECU • quick and cost-effective ECU remapping for using alternative fuels